Masses and couplings of vector mesons from the pion electromagnetic, weak, and πγ transition form factors - Melikhov, Dmitri; Nachtmann, Otto; Paulus, Timo (Arxiv, 2003)
We analyse the pion electromagnetic, charged-current, and $πγ$ transition form factors at timelike momentum transfers $q$, $q^2=s\le 1.4$ GeV$^2$, using a dispersion approach. We discuss in detail the propagator matrix of the photon-vector-meson system and define certain reduced amplitudes, or vertex functions, describing the coupling of this system to final states. We then apply the derived analytic expressions to the analysis of the recent